THE CONTRIBUTION OF MOTIVATION, CREATIVITY, AND VIRTUAL ENVIRONMENT TOWARDS THE PRODUCTIVITY OF DIGITAL NOVEL WRITERS ON NOVELTOON - Puput Nasoha Isnaeni; Iskandar Ali Alam (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Digital technological transformation has created broader opportunities for the development of digital-based literature, including through platforms such as NovelToon. The platform provides writers with opportunities to produce and distribute their works to a wider audience. However, this condition also requires writers to maintain high productivity in producing and consistently updating their works. Writer productivity can be influenced by various internal and external factors, including motivation, creativity, and the virtual environment. This study aims to examine and analyze the effects of motivation, creativity, and the virtual environment on the productivity of digital novel writers on NovelToon, both partially and simultaneously. This study employed a quantitative approach with an associative research design. The sample consisted of 40 active digital novel writers on NovelToon who were selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, and F-test. The findings demonstrate that motivation has a positive and significant effect on writer productivity. Creativity also has a positive and significant effect and represents the most dominant factor in increasing writer productivity. Furthermore, the virtual environment has a positive and significant effect on productivity. Simultaneously, motivation, creativity, and the virtual environment have a positive and significant effect on the productivity of digital novel writers on NovelToon. The simultaneous test produced an F-count of 184.454, which was higher than the F-table value of 2.87, with a significance level of 0.000. These findings indicate that writer productivity can be improved by strengthening motivation, developing creativity, and creating a supportive virtual environment. Therefore, writers should enhance their creative abilities and maintain consistency in producing works, while NovelToon managers can optimize digital features and facilities that support interaction, feedback, and the development of writers' works.